Corporate Environmental Disclosure: Exploring Real Earning Management, Governance, and Moderating Role of Audit Committees - Diah Hari Suryaningrum; Munari Munari (PT. Riset Press International, 2025)
In Indonesia, environmental disclosure remains limited due to the absence of clear guidelines for reporting corporate environmental performance. This study aims to examine the role of audit committees in reinforcing key factors influencing environmental disclosure. Using secondary data and a quantitative approach, the research focuses on 104 companies in the agricultural, basic industry, and chemical sectors listed on the Indonesia Stock Exchange (IDX). Through purposive sampling, 12 companies from the 2019-2023 period were selected, yielding a dataset of 60 observations. The study employs multiple linear regression for data analysis. Findings indicate that the board of commissioners’ size has a positive impact on environmental disclosure, whereas company size and real earnings management (REM) do not exhibit significant effects. Additionally, the audit committee does not moderate the relationship between these factors and environmental disclosure, except for the size of the board commissioner. These results suggest that corporate governance, particularly the structure of the board of commissioners with the audit committee, plays a crucial role in enhancing environmental reporting. However, the audit committee’s lack of moderation highlights the need for stronger regulatory frameworks and clearer responsibilities in corporate sustainability oversight. Policymakers and stakeholders may consider developing comprehensive guidelines to improve environmental disclosure practices across industries. This study contributes to the existing body of knowledge by shedding light on the specific governance structures that influence environmental disclosure in Indonesia, with a focus on the moderating role of audit committees in shaping disclosure practices.